Evaluasi Pelaksanaan Badan Layanan Umum Daerah (BLUD) pada Puskesmas di Kota Pekanbaru - Medy Surtiawaty; Jasrida Yunita; M. Kamali Zaman; Dendi Zulheri; Hetty Ismainar (LPPM Hang Tuah Pekanbaru, 2022)
(BLUD) of the public health center in Pekanbaru City is Pekanbaru Mayor Regulation No. 18 of 2017 concerning Systems and Procedures for Financial Management of BLUD public health centers in Pekanbaru City which was updated by Pekanbaru Mayor Regulation No. 187 of 2020 concerning Governance Patterns for Technical Implementation Units of Pekanbaru City Public Health Centers as Regional Public Service Agency (BLUD). There are 21 public health centers FKTP) under the supervision of the Pekanbaru City Health Office (. The purpose of implementing the Financial Management Pattern (PPK) of the Regional Public Service Agency (BLUD) at the Pekanbaru City Public Health Center is to improve health services for the community based on the principles of efficiency and productivity without prioritizing profit-seeking. The role of the Health Office is very important in supervising puskesmas in the BLUD Financial Management Pattern (PPK). To evaluate the implementation of the Regional Public Service Agency (BLUD) of the Public Health Center in Pekanbaru City. This type of research is qualitative with 5 main informants namely the head of the puskesmas and 2 supporting informants from the Pekanbaru City Health Office. Collecting data through in-depth interviews, observation, and document review. The triangulation used is the triangulation of sources, methods and data. Results of the regulation on the management of BLUD at the puskesmas referring to Permendagri No. 79 of 2018 and Perwako No. 187 of 2020. Dissemination of Regional Public Service Agency (BLUD) policies has been carried out but not routinely. There are constraints in terms of quantity and quality of human resources involved in the Financial Management Pattern (PPK) of the Regional Public Service Agency (BLUD). Adequate facilities and infrastructure, only management funds are not optimal. The majority of puskesmas do not have problems in the planning process, as evidenced by the fact that there are already documents for planning activities from the Regional Public Service Agency (BLUD) in each community health center. The implementation of the activities of the Regional Public Service Agency (BLUD) has not run optimally according to regulations. The function and role of supervision has not been well coordinated between the health office, the inspectorate, the Regional Financial and Asset Management Agency (BPKAD). Suggestion: optimizing the roles, functions and duties of the Pekanbaru City Health Office, the Regional Financial and Asset Management Agency (BPKAD) and the Inspectorate in the supervisory function and evaluating improvements for the activities of the Regional Public Service Agency (BLUD) at the Pekanbaru City public health center.